2001
DOI: 10.1056/nejmoa010399
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography of the Head before Lumbar Puncture in Adults with Suspected Meningitis

Abstract: In adults with suspected meningitis, clinical features can be used to identify those who are unlikely to have abnormal findings on CT of the head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
0
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 412 publications
(168 citation statements)
references
References 17 publications
1
158
0
9
Order By: Relevance
“…When this is suspected, rapid bedside evaluation and head CT are indicated. Several studies in patients with meningitis have suggested that CT should precede lumbar puncture in patients with signs such as optic disc edema, new seizures, or severe impairment of consciousness (see Table 10 in [65] for a succinct summary of contraindications to lumbar puncture) [134][135][136]. In practice, we find that most patients have had an initial CT scan in the emergency department prior to neurological evaluation.…”
Section: Edema and Herniationmentioning
confidence: 86%
“…When this is suspected, rapid bedside evaluation and head CT are indicated. Several studies in patients with meningitis have suggested that CT should precede lumbar puncture in patients with signs such as optic disc edema, new seizures, or severe impairment of consciousness (see Table 10 in [65] for a succinct summary of contraindications to lumbar puncture) [134][135][136]. In practice, we find that most patients have had an initial CT scan in the emergency department prior to neurological evaluation.…”
Section: Edema and Herniationmentioning
confidence: 86%
“…Third, the majority underwent cranial imaging (90%) and had normal results, despite the fact that only a minority of patients met imaging criteria. 1,17 Fourth, despite extensive diagnostic testing with current techniques, most of the patients (72%) had an unknown etiology.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Seizures, focal neurologic deficits, papilledema, and altered consciousness may predict increased ICP in the setting of normal-appearing radiologic images in acute meningitis. 1,6 While some experts propose that these clinical signs warrant performance of CT prior to LP, 7 others suggest that their presence should lead to deferment of LP. 1 The potential diagnostic uncertainty if LP is deferred may be mitigated by laboratory testing such as blood cultures (positive in 40%-50% of patients with meningococcal meningitis and 80%-90% with pneumococcal or Hemophilus meningitis).…”
Section: Sectionmentioning
confidence: 99%